2016
DOI: 10.1118/1.4964793
|View full text |Cite
|
Sign up to set email alerts
|

Transitional hemodynamics in intracranial aneurysms — Comparative velocity investigations with high resolution lattice Boltzmann simulations, normal resolution ANSYS simulations, and MR imaging

Abstract: A combination of MR derived data and CFD can be helpful in estimating the hemodynamic environment of intracranial aneurysms. Adequately resolved CFD would suffice gross assessment of hemodynamics, potentially in a clinical setting, and highly resolved CFD could be helpful in a detailed and retrospective understanding of the physiological mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 61 publications
1
24
0
Order By: Relevance
“…Several recent numerical studies have reported transitional flow in cerebral aneurysms, 16,18,19 and in this paper, we have shown that there is a difference between the assimilated solution and a corresponding high-resolution simulation that demonstrated transient to turbulent behaviour. There are two main reasons that transitional or turbulent flow is not captured by our assimilation procedure: (1) The resolution in space and time is too coarse and (2) transient and/or turbulent flow would likely require the simulation of many cardiac cycles, possibly combined with periodic boundary conditions.…”
Section: Conclusion Discussion and Future Workmentioning
confidence: 53%
See 1 more Smart Citation
“…Several recent numerical studies have reported transitional flow in cerebral aneurysms, 16,18,19 and in this paper, we have shown that there is a difference between the assimilated solution and a corresponding high-resolution simulation that demonstrated transient to turbulent behaviour. There are two main reasons that transitional or turbulent flow is not captured by our assimilation procedure: (1) The resolution in space and time is too coarse and (2) transient and/or turbulent flow would likely require the simulation of many cardiac cycles, possibly combined with periodic boundary conditions.…”
Section: Conclusion Discussion and Future Workmentioning
confidence: 53%
“…In contrast, the temporal resolution in CFD simulations is typically on the order of thousands of timesteps per second. As a result, there is often a notable discrepancy between CFD simulations and PC‐MRI measurements . To what extent these discrepancies arise from modelling errors, the spatio‐temporal averaging, or measurement errors is at present difficult to assess in particular because of the methodological challenge of incorporating the available data and control parameters in a simulation framework.…”
Section: Introductionmentioning
confidence: 99%
“…As a main numerical parameter driving the flow split between daughter branches, the outflow boundary condition often relies on a default zero pressure condition 17 which constitutes a potential source of errors. 5,18 A proper way to bypass this restriction consists in applying an outflow condition from measurements, although these latter are certainly not free of errors.…”
Section: Van Ooij Et In-vitro/vivo Intracranial Velocitymentioning
confidence: 99%
“…Further details on these aspects can be referred to in the works of Hasert et al 36,37 A specific verification of Musubi for transitional flows in physiologically realistic geometries can be found in references. 17,20,21…”
Section: Computational Detailsmentioning
confidence: 99%